2016
DOI: 10.4314/njb.v30i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological Response of <i>Capsicum annuum</i> L. Exposed to Simulated Acid Rain

Abstract: Pot experiments were carried out to evaluate the effects of simulated acid rain (pH 5.6 (control), 5.0, 4.0, 3.0, and 2.0) exposures on Capsicum annuum L. All pH levels with the exception of the control adversely affected all growth parameters (plant height, number of leaves, fresh and dry weight of leaves, root, stem and fruits, stem girth) of the plant. Leaf area and fruit production were also impacted. Nutritional analysis of the leaves revealed a decline with increasing acidity levels. Simulated acid rain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Acid rain generally slows plant growth by generating abnormalities in plant metabolism such as photosynthesis, chlorophyll content, nitrogen metabolism, and production of reactive oxygen species. Inversely, there are also exceptional cases of growth promotion [ 1 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Anatomically, acid rain can produce alterations of the cuticle thickness [ 28 , 29 ], cellular deformation and occlusion of stomatal cells, loss of trichomes in the epidermis, cell collapse in the mesophyll, and the formation of scar tissue [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acid rain generally slows plant growth by generating abnormalities in plant metabolism such as photosynthesis, chlorophyll content, nitrogen metabolism, and production of reactive oxygen species. Inversely, there are also exceptional cases of growth promotion [ 1 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Anatomically, acid rain can produce alterations of the cuticle thickness [ 28 , 29 ], cellular deformation and occlusion of stomatal cells, loss of trichomes in the epidermis, cell collapse in the mesophyll, and the formation of scar tissue [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Verma et al (2010) observed decreased growth and fruiting in three crops (Capsicum annuum, Lycopersicum esculentum and Solanum melongena) upon exposure to simulated acid rain (SAR). In a recent study on Capsicum annuum L., SAR with increased acidity levels has been shown to cause negative effects on the growth and exposure to SAR at pH 4 and below drastically suppressed growth characteristics (Bamidele and Eguagie, 2015). The present study aimed to assess the impact of simulated acid rain of different pH on budding, flowering, leaf abscission and pollen germination in sunflower (Helianthus annuus L., Family-Asteraceae), an important annual herbaceous oilseed and ornamental crop.…”
mentioning
confidence: 98%